2015
DOI: 10.1039/c5ra12000d
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of a carbon nanowall-based sensor for detection of organic vapours

Abstract: The high sensitivity in response, selectivity and reversibility was achieved on a carbon nanowall-based sensor for the vapor detection of volatile organic compounds, which were tested by an electrical resistance method during adsorption and desorption cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…CNW, also known as vertically oriented/aligned graphene sheets, are on long‐term stable, as far as structure and morphology are concerned, even when used in working devices. This nanomaterial has good durability over long‐time testing in acid solution, and functional stability when used in field emitters, electrodes for biosensors, and gas sensors, or as nanostructured electrodes in batteries, and supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…CNW, also known as vertically oriented/aligned graphene sheets, are on long‐term stable, as far as structure and morphology are concerned, even when used in working devices. This nanomaterial has good durability over long‐time testing in acid solution, and functional stability when used in field emitters, electrodes for biosensors, and gas sensors, or as nanostructured electrodes in batteries, and supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…The use of multilayer graphene oxide for water permeation and ion rejection has also been explored, both experimentally and numerically. , These works have shown that multilayering has the potential of improving desalination performance. Graphene membranes, which are vertically aligned to form carbon nanowalls, have also been successfully synthesized and used for various applications such as membranes, vapor detection, and energy storage. , …”
Section: Introductionmentioning
confidence: 99%
“…18,19 These works have shown that multilayering has the potential of improving desalination performance. Graphene membranes, which are vertically aligned to form carbon nanowalls, have also been successfully synthesized 20 such as membranes, 21 vapor detection, 22 and energy storage. 23,24 In our literature search, it was observed that a significant portion of works was based on purely numerical simulations, in particular molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…CNWs have also been used in energy storage, as electrodes for fuel cells, catalyst carriers, lithium-ion batteries or field emission devices [ 37 , 38 , 39 , 40 , 41 , 42 ]. In addition, the unique properties of CNWs make these electrodes an interesting starting material for the creation of electrochemical sensors for environmental, medical, and industrial analysis [ 21 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%